A study of the fusion of higher plant protoplasts - Withers, Lyndsey A. (1973)
Protoplasts and spontaneous fusion bodies can be isolated from a number of tissues, by treating the tissues with a mixture of macerating and cellulolytic enzymes. The shape of the spontaneous fusion bodies frequently reflects the parental tissue structure. An electron microscopic study of the treatment of the oat root tip and tobacco leaf with enzymes, reveals that spontaneous fusion is brought about by the expansion of plasmodesmatal connexions within the tissue. Specific treatments befo3B and during enzyme treatment can affect the level of spontaneous fusion. The culture of spontaneous fusion bodies in solid media is less successful than in liquid media, where cytoplasmic reorganization, wall regeneration and division occur. The pattern of division is irregular and may not be mitotic. The level of multinucleation in cultures declines with time. Whilst some spontaneous fusion bodies decline and others may subdivide, microdensitometric evidence suggests that nuclear fusion or close aggregation may be occurring. There is, however, no microscopic evidence for nuclear fusion. The fusion of originally separate, uninucleate protoplasts can be induced by treatment with sodium nitrate. Membrane adhesion and fusion are followed by organelle redistribution and vacuolar fusion. No interspecific fusion bodies are formed and the intraspecific fusion products demonstrate a low viability. Other salts induce protoplast adhesion and abnormal plasmalemmar activity but not fusion. Similarly, Concanavalin A and lysozyme induce strong adhesion but no fusion. Treatment of protoplasts with Sendai virus can induce adhesion and eventual lysis, with membrane fusion as a likely intervening stage. Lysolecithin induces a similar reaction. It is possible that such reactions could be controlled to successfully induce protoplast fusion.